MOTIF AUDIENCE DALAM MENONTON SINETRON ANAK JALANAN: STUDI DESKRIPTIF PADA IBU-IBU TAMBAK SAWAH RT.02 RW.01 KECAMATAN WARU KABUPATEN SIDOARJO - Azimatul, Alfirda Nur; Sudaryanto, Edy; Soenarjanto, Bagus (representamen, 2017)
This study examines a motive Audience in watching soap operas on the Street ChildrenMothers wherein Street Children soap is soap opera RCTI impressions are much favored the womenespecially mother.Purpose of this study was to determine the motive Audience especially mothers inChildren watch soap operas street.Type research is descriptive qualitative research subjects of tenaudience which aims to determine the motives of whatever is on the audience, while the datacollection techniques used were interviews and observations. The results of this study stated that tenaudience of three motives motifs cognitive, affective motives and the motives of diversion Motif andMotif Diversi Affective most dominates to the informer and the rest Cognitive motif that dominates theaudience.Keywords: Motif, Audieance, Soap Opera, Media, Television, Sidoarjo